O mais profundo é a festa: cartografias dos jogos performativos e da carnavalização em Belo Horizonte após a Praia da Estação - Thálita Motta Melo (2019)
The present thesis is a cartography research that initiates from imaginative breach of Praia da Estação (2010), in which the substances belonging to the process of Carnival creates the performative scenes in its current period of time – parties, performances, Carnival blocks, communitas, duels. This thesis reflects on the aesthetic and political denominators shared by the mapped scenes, such as the substances of joy, laughter, play, described as forms of roleplaying in some layers of the city of Belo Horizonte. All these substances of the process of Carnival were followed, like an a spiral, to compose the idea of performative plays: the joy as a strategy to persevere while existing, the party as a form of performing the joy of political bodies, the laughter as the ocean spring in the process of Carnival, and the process of Carnival as a public space phenomenon, and the public space phenomenon as a synthesis of occidental cities, the playful as resistance politics, the play as the social structuring of the playful, the ritual structure of the play as a performative aesthetic, the performative play of political bodies in the city: joy, party, laughter, city, playfulness, performance and politics. Through the choice for cartography as a method, the curvatures of the spiral were formed in a process towards the bricolage method, starting from the heteroclite cutouts, from the gathering with the movements, with cultural agents, performers, and the parties connected directly or indirectly with the process of Carnival after Praia da Estação, or with the ones that made me come closer with the city experience; and so, this thesis presents an hybrid methodology. At last, this thesis weaves a conclusion from the setback of performativity, while it maps the aestheticization of politics and the politization of art produced since Brazil’s recent political and media-influenced coup, in a way to propose the dissensual aspect of this thesis.